1979
DOI: 10.1139/v79-307
|View full text |Cite
|
Sign up to set email alerts
|

Determination of solubility products of hydroxylapatite, chlorapatite, and their solid solutions

Abstract: Solubility equilibria of hydroxylapatite, chlorapatite, and a series of their solid solutions were investigated at 37 °C in the pH range 4.25 to 7.40 and their solubility products evaluated. Proof could be obtained for their stoichiometric dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Chlorapatite is known to exhibit excellent durability in aqueous solution over a range of pH [58]. The particulate products obtained through the solid state reaction process reported here also offer excellent leach resistance in deionized water at 40°C, as summarized for the radioactive Type I PuCl 3 and AmCl 3 containing ceramic in Table 3, and for the non-radioactive Type II, III and IV containing ceramics in Table 4.…”
Section: ð8þmentioning
confidence: 87%
“…Chlorapatite is known to exhibit excellent durability in aqueous solution over a range of pH [58]. The particulate products obtained through the solid state reaction process reported here also offer excellent leach resistance in deionized water at 40°C, as summarized for the radioactive Type I PuCl 3 and AmCl 3 containing ceramic in Table 3, and for the non-radioactive Type II, III and IV containing ceramics in Table 4.…”
Section: ð8þmentioning
confidence: 87%
“…Although the calcific deposits consist of apatitic calcium phosphate (HAP containing mainly carbonate, fluoride, magnesium and sodium) the formation of transient precursor phases such as DCPD and OCP is possible, as in vitro studies have shown (Brown et al, 1957;Heughebaert et al, 1983;Moreno & Varughese, 1981). The formation of calcium phosphates on porcine heart valves to a percentage of 30-50% is responsible for their dysfunction after 12-15 years due to stenosis or insufficiency (Narasaraju & Rao, 1979). Despite the fact that the thermodynamic driving force in blood serum for nucleation and growth is sufficiently high for the homogeneous formation of calcium phosphates, the process is believed to be heterogeneous as dead cell remnants, lipids or degenerative collagen fragments may provide active sites for heterogeneous nucleation.…”
Section: Crystal Growth In Heart Valvesmentioning
confidence: 99%
“…At AWE the approach was to immobilize the chloride in a stable calcium phosphate host that was also capable of immobilizing the actinide cations. Apatite is a naturally occurring mineral of general formula, A 5 (BO 4 ) 3 (OH,F,Cl), where A can be a variety of 1-3 valent cations including Ca, Ba, Na, Pb, Sr, La or Ce and B is commonly P, V or As [1] although Terra et al reports that tri-and tetra-valent cations require a coupled substitution (Ca,PO 4 ) M (An,SiO 4 ) [2]. They are highly non-stoichiometric, with vacancies, Ca deficiencies, excess of (PO 4 ), etc.…”
Section: Introductionmentioning
confidence: 99%